2020
DOI: 10.1111/spol.12602
|View full text |Cite
|
Sign up to set email alerts
|

Why do unemployed people avoid participation in training? An experiment for policy making

Abstract: Despite active labour market policies being implemented to increase the skills and job opportunities of the unemployed, the number of people who do not participate in training and other services of job orientation remains high. By providing a model that studies the decision-making process of a potential participant, we hypothesise there is a behavioural motive behind it. An experiment is carried out to account for both the individual's preference and the social expectations of agents such as the government and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…A study by Focacci and Lam (2020) showed that young adults are very susceptible to their peers when it comes to deciding whether to participate in an employment programme. This is an important practical implication, as frontline workers can have numerous effective interventions at their disposal, but when no one participates in them, youth unemployment will remain an issue (e.g., Grandia, La Grouw, & Kruyen, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Focacci and Lam (2020) showed that young adults are very susceptible to their peers when it comes to deciding whether to participate in an employment programme. This is an important practical implication, as frontline workers can have numerous effective interventions at their disposal, but when no one participates in them, youth unemployment will remain an issue (e.g., Grandia, La Grouw, & Kruyen, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that willingness to participate in training programmes is e.g. depending on social and governmental expectations, with social expectations being the most powerful (Focacci & Lam, 2020). This could potentially explain the low willingness for participation among the age group 55+, as there might be social expectations about education and development of older workers that could inhibit their willingness to participate in training programmes.…”
Section: Men At Least 5 Days Of Paid Education Men Any Paid Educationmentioning
confidence: 99%
“…Having a place to go (the projects) gave them a reason to go outside and meet others and a chance to feel welcome. Focacci and Lam (2020) suggest that peer pressure can also have a negative effect on the willingness of the young unemployed to participate in a training programme of active labour market policy, and that social identity is of great importance. Meeting other people was important for them as socializing made them feel more dignified as opposed to feeling lonely.…”
Section: A Sense Of Togethernessmentioning
confidence: 99%